Preparation and characterization of PLD deposited Indium Selenide thin film - Khaled Z. Yahea; Amar H. Jareeze; Heba Salam Tariq (Engineering and Technology Journal, 2014)
Indium Selenide films were deposited by pulsed laser deposition (PLD) with a Nd-YAG laser under vacuum condition. During the deposition, the substrates were kept at room temperature. The typical thicknesses of films were 200nm, 800 nm. The films were analyzed by X-ray diffraction for the crystallographic, the surface morphology of the film were investigated by AFM. It has been observed that grain growth depend on film thickness. The optical properties were characterized in the ultraviolet–visible region employing optical transmission, absorption, band gap. The direct optical band gap value for the films was found to be of the order of (2.2, 2.1) eV for thickness (200,800) nm respectively at room temperature.